Vincristine‐induced neuropathy in pediatric patients with acute lymphoblastic leukemia in Oman: Frequent autonomic and more severe cranial nerve involvement. Issue 12 (17th June 2017) - Nazir, Hanan F.; AlFutaisi, Amna; Zacharia, Mathew; Elshinawy, Mohamed; Mevada, Surekha T.; Alrawas, Abdulhakim; Khater, Doaa; Jaju, Deepali; Wali, Yasser
Abstract: Background: Vincristine (VCR) induced peripheral neuropathy is a common complication in children with acute lymphoblastic leukemia (ALL). Procedures: A retrospective data analysis over an interval of 10 years (2006–2016) of all children with ALL seen at Sultan Qaboos University Hospital was carried out. Electronic medical records of eligible patients were reviewed. Patients with clinical evidence of neuropathy and abnormal nerve conduction studies (NCSs) were included in the study. Results: Nineteen (nine females and 10 males) out of 103 pediatric patients developed VCR‐related neuropathy, and their age ranged between 2.5 and 14 years. Symptoms started after 2–11 doses of VCR. All 19 patients had documented peripheral neuropathy on NCSs. The autonomic nervous system and cranial nerves affection was relatively common in our patients; two presented with bradycardia, two patients with unexplained tachycardia, and five had abdominal pain and constipation, complicated by typhlitis in two patients. One patient developed unilateral hearing loss. Two patients developed severe life‐threatening cranial nerve involvement with bilateral ptosis and recurrent laryngeal nerve involvement presented as vocal cord paralysis, hoarseness of voice, frequent chocking, and aspiration episodes. Conclusions: Peripheral neuropathy was the commonest form of VCR‐related neuropathy. Autonomic neuropathy was relatively common in our patients. Cranial neuropathy is a serious side effect of VCR that can be severe, involving multiple cranial nerves and needs prompt recognition and management. Concomitant administration of pyridoxine and pyridostigmine does not seem to protect against further neurological damage in some patients.